Advancements in six-membered cyclic carbonate (1, 3-dioxan-2-one) synthesis utilizing carbon dioxide as a C1 source. Issue 32 (16th May 2018) - Hosseinian, Akram; Farshbaf, Sepideh; Mohammadi, Robab; Monfared, Aazam; Vessally, Esmail
Abstract : This review article surveys literature methods for the synthesis of six-membered cyclic carbonates using various substrates in the presence of CO2 with special emphasis on the mechanistic aspects of the reactions. Abstract : This review article surveys literature methods for the synthesis of six-membered cyclic carbonates using various substrates in the presence of CO2 with special emphasis on the mechanistic aspects of the reactions. We have classified these reactions based on the type of starting material.